The Four-Part Literature Review Process: Breaking It Down for Students. Issue 2 (3rd April 2017) - Price, Rebecca H.
ABSTRACT: Both undergraduate and graduate students face similar challenges when tasked with writing literature reviews. Breaking down the literature review into a four-part process helps students decrease frustration and increase quality. This article provides usable advice for anyone teaching or writing literature reviews. Tips and illustrations illuminate each part of the process, including 1) Developing a Topic; 2) Searching the Literature; 3) Narrowing the Scope; and 4) Synthesizing Prior Research. First, practical tips for topic development include welcoming change and exercises for allowing students to "talk out" topic evolution in physical or virtual settings. Next, tips for searching include defining quality research in the discipline, linking to online tools, refining language, and working with that first good article. Then, practical tips for narrowing include advice for deconstructing articles and questions to ask when "talking out" refinement of the project. Finally, practical tips for synthesizing include virtual tagging and physical clustering exercises.